PANDANGAN ORIENTALIS TERHADAP SEJARAH ISLAM AWAL - Rizki Ulfahadi; Reynaldi Adi Surya (Ushuluna: Jurnal Ilmu Ushuluddin, 2018)
Islamic Studies in the Western have different view and method from Eastern Islamic studies (such as Arab or Indonesia). The orientalists researched Islam through critical and historical views. One of the topics discussed in this paper is "Early Islam" or "Old Islam" problem, the origin of prophet Muhammad SAW, the origin of the word "Islam", and etc. We explain their opinions about Muslim scholars’ construction of the early Islam.